Pesan Nonverbal pada Love Languages dalam Film The Wind Rises Karya Hayao Miyazaki - Mahapurnayanti, Anak Agung Sagung Istri Pradnya (Japanese Literature Study Program, Faculty of Letters, Dr. Soetomo University, 2024)
Love languages are communication patterns in relationships used to convey feelings to someone special. Acts of love languages often appear in non-verbal behaviors that strengthen relationships and help partners get to know each other. According to Gary Chapman, there are five types of love languages. Love languages behaviors are often seen in the film The Wind Rises by Hayao Miyazaki, which was chosen as the data source for this research.This research uses a descriptive analysis method to identify the categories, meanings, and functions of non-verbal messages in love languages actions in the film The Wind Rises, based on Yule's pragmatic theory (1996), Chapman's love languages theory (2010), Richmond and McCroskey's nonverbal message categories theory (2004), Danesi's semiotic theory (2011), and Knapp's non-verbal message functions theory (1978).The data analysis results show that the film The Wind Rises includes four of the five types of love languages: 1) words of affirmation, 2) acts of service, 3) quality time, and 4) physical touch. The film also fulfills six of the eight categories of nonverbal messages: 1) gestures and body movements, 2) facial and eye behavior, 3) vocal behavior, 4) time, 5) touch, and 6) environment. The meanings of non-verbal messages are influenced by the situation and condition of the interactions between the characters, such as sincerity, trust, harmony, and closeness. Their functions include: 1) complementing, 2) substituting, and 3) repeating. Keywords: love languages; nonverbal actions; nonverbal messages.